Adjuvant treatment of breast cancer patients with trastuzumab - Matos, Erika (Radiology and oncology (Ljubljana), 2007)
Background. Trastuzumab is a monoclone antibody directed against HER2 receptors that are overexpressed in approximately 20% of breast cancer patients. The present paper presents five clinical trials in which trastuzumabwas applied in breast cancer patients in adjuvant setting. The results of all the trials consistently demonstrate a high efficacy of this target drug in the patients with HER2 positive tumours. So far, no formal guidelines for using trastuzumab in adjuvant setting for breast cancer have been approved. The reasons are many: (i) mean observation time in the studies done so far was considerably short; (ii) the drug was used according to different schedules, (iii) the overall time of treatment with trastuzumab was different in each trial, (iv) late side effects of treatment with trastuzumab are inadequately investigated, and (v) nobody can so far say for sure for which HER2 status patients therapy with trastuzumab is really beneficial. Conclusions. Trastuzumab is definitely very helpful in the treatment of the HER2-positive breast cancer patients that are hormone-independent and of anatomically larger tumours; but, what the absolute benefit of trastuzumab therapy in the treatment of small hormone-dependent tumours is remains a mystery. Incidentally, it must be borne in mind that cardiotoxicity, the well known side effect, may put particularly elderly patients at risk of death, thus beating any treatment advantages down. It has also not been yet resolved at what time it would be most appropriate to start with the therapy with trastuzumab, what would be the optimal duration of the therapy and whether trastuzumab is to be administered concurrently with chemotherapy or immediately after it? What is the optimal treatment duration, one or two yearsor only a few months? In addition there is still a question of optimal HER2 status determination and which HER2 status predicts for trastuzumab benefit. (Abstract truncated at 2000 characters)
Keywords: Antagonists And Inhibitors; Antibodies, Monoclonal; Breast Neoplasms; Dojka, novotvorbe; dojke; Drug Therapy; novotvorbe; Protitelesa monoklonska; Proto-Oncogene Proteins C-Erbb-2; rak (medicina); zdravljenje